Association of resilience with caregiver burden in caring for the elderly in stroke; a systemic review - Chen, Hongyun; Makhdzir, Norafisyah; Wei, Chao Loh (Rawal Medical Journal, 2024)
Objective: To review the construct of resilience and related variables in caregivers caring for older adults with stroke and factors influencing caregiver burden. Methodology: The review included studies published between February 2009 and February 2024, using the Preferred Reporting Items for Systematic Reviews. The PubMed, Web of Science, Scopus, China Academic Journals, Wan Fang Data Knowledge Service Platform, China Science and Technology Journal Database databases were employed. Results: In all 18 investigations, 14 quantitative and 2 qualitative were found. Resilience was linked to positive impacts on life satisfaction and emotional pain in these studies. Building robust coping skills can be facilitated by social support and communication. The majority of the chosen papers employed convenience sampling. Semi-structured interviews were utilized to gather qualitative and quantitative data utilizing resilience-related elements and evaluation tools. Conclusion: Encouraging caregivers to adopt a resilient coping style helps them feel less distressed about changes in their biopsychosocial and spiritual aspects that come with sickness. A resilient coping strategy can help the caregiver adjust while lowering their risk of stress and strain.